The Idea of Man in Munir Niazi's Ghazals - Arifa Batool (بازیافت)
Munir Niazi was a well knowned modern urdu poet. This article deals with man as a subject of his poetry. He exposes the materialistic selfish man of machine era. In his Ghazals, sensitive man, despite ostensible charms of metropolitian life, has been depicted as burdened with fear, lonliness and tiresome. Yet, man is optimistic about his future in this suffocating and tense environment.